Peranan Guru dalam Membina Akhlak Santri Di Pondok Pesantren Muhammad Amin Rajo Tiangso, Jangkat Timur - Idma Rizal (Prodi Bimbingan dan Konseling Islam (BPI) Fakultas Dakwah UIN Sulthan Thaha Saifuddin Jambi, 2021)
The background of this research is that it pays attention and requires attention, namely the phenomena that occur in Islamic boarding schools, especially Islamic boarding schools. M. Amin rajo poleso. This thesis focuses on how the role of ustad/ustadzah in fostering the morals of students at the M.Amin rajo poleso Islamic boarding school, what factors support and hinder the role of the ustadz/ustadzah in fostering the morals of students in the Muhammad Amin rajo poleso Islamic boarding school. And research. This type of research is field research. In an effort to obtain the information and data needed as materials for this thesis, this research approach uses a qualitative method. The results of the study found that the strategy of ustadz/ustadzah in Islamic boarding schools varied by carrying out the stages and methods that had been determined as much as possible in order to achieve the desire to produce students who had good morals, became role models for recording, advising, teaching the sciences of morality. While the factors that hinder and support are the existence of students who are still enthusiastic in studying at this Islamic boarding school, and there are sufficient books, there are adequate places of worship, and so on, the factors that hinder are inadequate teaching and learning facilities and infrastructure, and few classrooms, lack of qualified teachers pengajar professionals and so on.